2019
DOI: 10.1093/rheumatology/kez335
|View full text |Cite
|
Sign up to set email alerts
|

Unique Sjögren’s syndrome patient subsets defined by molecular features

Abstract: Objective To address heterogeneity complicating primary SS (pSS) clinical trials, research and care by characterizing and clustering patients by their molecular phenotypes. Methods pSS patients met American–European Consensus Group classification criteria and had at least one systemic manifestation and stimulated salivary flow of ⩾0.1 ml/min. Correlated transcriptional modules were derived from gene expression microarray data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 38 publications
3
32
0
1
Order By: Relevance
“…Interestingly, our study found a strong correlation between CTA-250D10.23 and CXCL13. Serum CXCL13 is a biomarker of salivary gland local pathology (37) and local increased of CXCL13 also serves as one of features of the pSS patient subset (38). As an echo to these lines of evidence, CXCL13 was identified as the most robustly up-regulated gene in pSS (Supplemental Figure 1).…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, our study found a strong correlation between CTA-250D10.23 and CXCL13. Serum CXCL13 is a biomarker of salivary gland local pathology (37) and local increased of CXCL13 also serves as one of features of the pSS patient subset (38). As an echo to these lines of evidence, CXCL13 was identified as the most robustly up-regulated gene in pSS (Supplemental Figure 1).…”
Section: Discussionmentioning
confidence: 94%
“…Thereby, pSS patients could be stratified in interferon negative, Type I or Type I + II positive subgroups with higher prevalence of anti-SSA and anti-SSB among those with IFN activation without relation with systemic activity. Another group 42 performed a clustering analysis of blood gene expression microarray which classified the 47 pSS patients in three clusters characterized by IFN and inflammation with no discriminant clinical features Moreover, four subgroups of patients with similar patients’ clinical characteristics were identified based on absolute cell counts per μL of blood 23 . Lastly, a stratification based on patient clinical phenotypes characterized a posteriori at the molecular level was proposed 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Both studies confirmed that protein microarrays are capable of higher sensitivity than ELISA. In recent years, similar multiplex approaches were developed to screen specific autoantibody biomarkers for various AIDs, such as rheumatoid diseases ( 71 , 72 ), type 1 diabetes ( 73 ), lupus nephritis ( 74 ), multiple sclerosis ( 75 , 76 ), systemic sclerosis ( 46 ), SLE ( 37 , 77 , 78 ), juvenile dermatomyositis ( 67 ), and Sjogren's syndrome ( 79 ). Importantly, most of these studies included dozens to several hundreds of autoantigens.…”
Section: Development Of Antigen Arraysmentioning
confidence: 99%
“…Importantly, most of these studies included dozens to several hundreds of autoantigens. In addition, a multiplexed, bead-based system was developed that is also suitable for array construction and detection for this application ( 79 ). However, only a few of the most well-studied autoantigens were used to construct this detection system for screening autoantibodies in patients' sera.…”
Section: Development Of Antigen Arraysmentioning
confidence: 99%